Exploring the impact of hybrid and remote work models on business efficiency and employee well-being: a scoping review - Selvaraju, Pravina; Mohd Anuar, Mohd Ashraff (Human Resources Management Academic Research Society (HRMARS), 2024)
The pandemic of COVID-19 has drastically emphasized the importance of hybrid/remote work arrangements even though these have existed in the market beforehand. The aim of this scoping review is to investigate and analyze the impact of hybrid and remote work models on both business efficiency and employee well-being across various industries and organizational settings. By mapping the existing literature. A total of 17 published papers with inclusion and exclusion criterias. To assess the quality of the articles, the author used Methodological Quality Questionnaire (MQQ) scoring. The findings indicate that there are positive significant relationships among hybrid and remote work models on business efficiency and employee well-being.